(untitled) (Research, Society and Development, 2022)
This research was developed to answer questions that took shape during the author’s academic career, after he noticed an improvement in his mathematical abilities during his journey in a higher degree in computer science, with this the general objective of this research was to verify the benefits that could be noticed through the bibliographic research raised. While the data were collected, the questions that the author considered of fundamental importance for the research and that guided the subjects discussed here were: What is the difference between the current practice of teaching mathematics and a teaching based on the use of programming language resources? What benefits can programming bring to the student’s life inside and outside the classroom? This work focused mainly on mathematics classes and their technologies, in view of the increasing use of traditional computers and microcomputers in the most diverse instances of society and the possibilities that these devices bring, using them in the educational environment becomes of paramount importance in student preparation. In this context, using the mathematical concepts that are within computer programming can be of great help for a more practical education, in addition to the fact that combined with the contribution of the subject to attract a lot of interest from students, since it involves new technologies. and the possibilities of creating games and computer programs, subjects that are intrinsic to our daily lives today.